RESEARCH REVIEW ON THE ANALYSIS OF NEWS FRAMING OF INDONESIAN PRESIDENTIAL ELECTION 2005-2021 - Dafrizal Samsudin (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2022)
This study aims to determine the development of news framing research in the Indonesian presidential election in 2005-2021. A total of 38 scientific works consisting of undergraduate thesis, master's thesis, and journals were analyzed using the principle of a systematic literature review. The analysis shows that there are more scientific research papers in the form of undergraduate thesis compared to journals and master's thesis. Research trends increased dramatically in 2017-2021, with more portal media studies than other media. Zhongdang Pan and Gerald M. Kosicki framing analysis models are commonly used. Many media take sides in reporting on presidential and vice-presidential candidates compared to neutral and balanced ones. The framing influencing factors of the Indonesian presidential election news are media ideology, the background of journalists and news editors, media routines, media organizations, extra media, selection of syntactic, script, thematic, and rhetorical structures of news, selection of sources, the role of media owners, background selection of sources.